Pengaruh Circuit Training Terhadap Peningkatan Daya Tahan Otot Tungkai Dan Kelincahan Pada Pemain Futsal Beka United Futsal Academy - Mubarokah, Nisa'ul; Sugiono, S.Fis.,M.H.Kes (2017)
ABSTRACT Background: Futsal is a game that is done quickly and dynamically in terms of a very small pitch almost no room to make mistakes. The physical components of futsal players including leg muscle endurance and agility. To improve both can use the method of circuit training, a series of physical exercises thorough which the contents of adjusting the exercise of the goals to be achieved. Objective: This study aimed to determine the effect of circuit training to increase leg muscle endurance and agility in futsal players. Methods: This research method using quasi-experimental. The study design used is non equivalent control grub. Sampling using purposive sampling method that meets the criteria of inclusion and exclusion. The samples used 20 people. Results: The data were normally distributed, statistical test to test the effect of using a paired sample t-test. with a p-value results in leg muscle endurance 0.000 (<0.05) and the agility of 0.000 (<0.05). To test the effect of different using independent t-test test with results in leg muscle endurance 0.000 (<0.05) and the agility of 0.31 (<0.05). Conclusion: With these results we can conclude that there is an increase leg muscular endurance and agility after administration of circuit training in futsal players. Keywords: circuit training, leg muscle endurance, agility.